2021
DOI: 10.25046/aj060277
|View full text |Cite
|
Sign up to set email alerts
|

The Context of the Covid-19 Pandemic and its Effect on the Self-Perception of Professional Competences by University Students of Business Administration

Abstract: This article aims to determine to what extent the self-perception of acquiring professional skills has been affect ed, by the context of the Covid-19 pandemic in University Students of Business Administration; For which, the results obtained in two satisfaction survey processes, carried out in academic semesters 2019-B and 2020-A, have been compared, marking a before and after in relation to the declaration of a state of emergency in Peru. Initially, it was determined that the indicators "To solve specialty ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…An important aspect is the results that show that the percentage of student satisfaction was found to increase slightly during virtual learning in all indicators; This is due to the fact that although it was abruptly to move from the face-to-face to the virtual, the response of the university institution allowed to guarantee the continuity of the educational service, through the implementation of a virtual platform, whose functionality and operation, turned out to satisfy the expected demand for the students. In this regard, in [12], the author points out that the declaration of the state of emergency did not allow the development of aspects associated with the virtual teaching-learning process in a planned and structured way, however the universities made necessary efforts, which led to the implementation of learning environments virtual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect is the results that show that the percentage of student satisfaction was found to increase slightly during virtual learning in all indicators; This is due to the fact that although it was abruptly to move from the face-to-face to the virtual, the response of the university institution allowed to guarantee the continuity of the educational service, through the implementation of a virtual platform, whose functionality and operation, turned out to satisfy the expected demand for the students. In this regard, in [12], the author points out that the declaration of the state of emergency did not allow the development of aspects associated with the virtual teaching-learning process in a planned and structured way, however the universities made necessary efforts, which led to the implementation of learning environments virtual.…”
Section: Discussionmentioning
confidence: 99%
“…The following figure shows the indicators of teacher performance that have been considered in the satisfaction survey. These indicators are part of the data collection instrument, used and validated in research carried out in the context of the health emergency, as evidenced in [12] and [13]. It should be noted that the application of the data collection instrument was carried out at the end of the academic semesters; this criterion is used with the purpose that the student has a greater spectrum of experiences acquired based on the teaching performance in the context of virtual teaching.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, students who have completed a remote internship during the COVID-19 pandemic have experienced working conditions that will shape positively their professional future by closely reflecting the future office working conditions [4]. Finally, it was found that business students have been affected by the context of the COVID-19 pandemic in acquiring professional skills, suggesting that students are missing important skills after graduating [40].…”
Section: Influence Of the Covid-19 Pandemic On Studentsmentioning
confidence: 99%